2017
DOI: 10.18393/ejss.284266
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of soils with Cu, Na and Hg due to the highway and railway transport

Abstract: Article Info Received : 09.05.2016 Accepted : 20.07.2016 Contamination of soils with three metals due to the highway and railway transport was studied. Copper was selected as a suitable indicator for both kinds of transportation. Sodium served to assess the level of contamination resulting from the road salting in winter. Mercury was determined in samples taken close to the railway in order to test its release from impregnated wooden ties. All analytes were determined using the methods of the trace element an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Complex studies of the Cd pollution have shown that in order to reduce the negative impact on the environment, that the safe distance from the railway stations are up to 15 m. Therefore, based on the research of the scientists, it can be stated that it is necessary not only to monitor the distribution of Cd in different soil profiles, but also to monitor the morphological properties of the soil, its granulometric composition and higher concentration of humus, clay, minerals, phosphate and carbonate ions in the soil. Complex studies have confirmed that the contaminate levels of Cd increased with the operation time of the railway lines (Stojic et al 2017;Šeda et al 2017;Zhang et al 2012;Chen et al 2014).…”
Section: Determining CDmentioning
confidence: 93%
See 2 more Smart Citations
“…Complex studies of the Cd pollution have shown that in order to reduce the negative impact on the environment, that the safe distance from the railway stations are up to 15 m. Therefore, based on the research of the scientists, it can be stated that it is necessary not only to monitor the distribution of Cd in different soil profiles, but also to monitor the morphological properties of the soil, its granulometric composition and higher concentration of humus, clay, minerals, phosphate and carbonate ions in the soil. Complex studies have confirmed that the contaminate levels of Cd increased with the operation time of the railway lines (Stojic et al 2017;Šeda et al 2017;Zhang et al 2012;Chen et al 2014).…”
Section: Determining CDmentioning
confidence: 93%
“…Analogously performed and previously discussed Pb pollution studies, complex studies of the Zn pollution have shown that in order to reduce the negative impact on the environment, that the safe distance from the railway stations are up to 10…15 m. Therefore, based on the research of the scientists, it can be stated that it is necessary not only to monitor the distribution of Zn in different soil profiles, but also to monitor the morphological properties of the soil, its organic matter content and granulometric composition (Stojic et al 2017;Šeda et al 2017;Zhang et al 2012;Chen et al 2014).…”
Section: Determining Znmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest copper content was observed in soils taken close to the railroad. [13] Railway tracks on the territory of Srem, Serbia…”
Section: Study Area Main Conclusion Referencesmentioning
confidence: 99%
“…Scientists are increasingly paying more attention to the source of many contaminants from the railway. The PHEs can be connected with, i.e., abrasion of wheels and rails or even with the materials that conserve railway sleepers [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%